Effects of DS‐modified agarose gels on neurite extension in 3D scaffold through mechanisms other than changing the pore radius of the gels. Issue 7 (7th August 2013) - Peng, Jin; Pan, Qian; Zhang, Wei; Yang, Hao; Zhou, Xue; Jiang, Hua
Abstract Dermatan sulfate is widely distributed as glycosaminoglycan side chains of proteoglycans, which are the main components of glial scar and inhibit neurite regeneration after nerve injury. However its role in the inhibiting process is not clear. Understanding neurite extension in three‐dimensional scaffolds is critical for neural tissue engineering. This study used agarose gels modified with dermatan sulfate as the three‐dimensional culture scaffold. We explored structure–function relationship between the three‐dimensional scaffold and neurite extension and examined the role of dermatan sulfate on neurite extension in the three‐dimensional scaffold. A range of agarose concentrations was used to generate varied gel physical structures and the corresponding neurite extension of embryonic day (E9) chick dorsal root ganglia was examined. We measured gel stiffness and gel pore size to determine whether dermatan sulfate changed the gels' conformation. As gel concentration increased, neurite length and gel pore size decreased, and gel stiffness increased. At 1.00 and 1.25% (wt/vol) concentrations, dermatan sulfates both immobilized with agarose gels and dissolved in culture medium inhibit neurite extension. While at 1.50 and 1.75% (wt/vol) concentrations, only immobilized dermatan sulfate worked. Immobilized dermatan sulfate could modify molecular shape of agarose gels, decrease gel pore size statistically, but did not influence gel stiffness. We have proved that the decrease of gel pore size is insufficient to inhibit neurite extension. These results indicate that dermatan sulfate inhibits neurite extension not through forming a mechanical barrier. Maybe its interaction with neuron membrane is the key factor in neurite extension. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2157–2162, 2014.